Video Animasi Kisah Atlantis Land untuk Meningkatkan Daya Tarik Diorama Atlantis Land - Septian Anom Atmojo; Aditya Rahman Yani; Widyasari (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2021)
The development of facilities and infrastructure that follows the development of modern technology is very important for the development of a theme park. One of the theme parks in Surabaya that has great potential is Atlantis Land which has a beautiful diorama which is located in front of the entrance to Atlantis Land. As the main attraction, the Atlantis Land Diorama plays an important role in providing information about the amazing story behind Atlantis Land. The design of this animated video intends to give a new attraction to the Atlantis Land diorama by telling the story behind Atlantis Land in a modern animation style. This design uses several data collection methods, namely in-depth interviews, observations and questionnaires. After the data is collected, it is analyzed using descriptive analysis method to look for ideas in formulating interesting animated videos. The design concept chosen was